Pengaruh modifikasi lift camshaft dengan bahan bakar pertalite dan pertamax terhadap kinerja mesin 110 cc - Wahyu Nur Achmadin; Indah Noor Dwi Kusuma Dewi; Djoko Wahyudi (Universitas Muhammadiyah Metro, 2021)
Modification of the camshaft lift with pertalite and pertamax fuel has been carried out. This study aims to determine the effect on engine performance, namely a change in lift of 1 mm is able to maximize performance to be better than the standard. In this study using a 110cc motorcycle engine with pertalite and pertamax fuels to show a comparison of modifications to the standard. The results obtained are the modified 1mm lift camshaft with Pertamax fuel produces maximum power and torque compared to the standard camshaft, with values of 13.33 hp and 13.38 Nm, respectively. The highest increase in power and torque on pertalite fuel is found at 7000 rpm which can increase performance by 7.4% and 7.2%, respectively, from the standard camshaft. Meanwhile, the highest increase in power on Pertamax fuel was obtained at 5500 rpm rotation with a value of 12.1% while the highest torque increase in Pertamax fuel was obtained at 8000 rpm rotation with a value of 11.9%.